Anaesthesia for emergency care - Nolan, Jerry; Soar, Jasmeet ([Oxford] : Oxford University Press, 2012)
Written for use in the emergency department and for emergency surgery, this concise handbook covers the provision of all aspects of anaesthesia in an urgent setting.
Specialized.
Description based on online resource; title from home page (viewed on July 26, 2012).
Includes bibliographical references and index.
Keywords: Anesthesia; Emergency medicine